Drug Resistance in Mycobacterium Tuberculosis Isolates to Isoniazid and Rifampin - M Pourhajibagher (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Tuberculosis is the most dangerous infectious disease in the world today. Rifampicin (RMP) and Isoniazid (INH) are the two most important first-line anti-tuberculosis drugs for the treatment of tuberculosis. Resistance to these drugs has been increased in most of countries. The aim of this study was evaluation of drug resistant in mycobacterium tuberculosis isolates to Isoniazid and Rifampin in patients that referred to health care center of Mazandaran province, Iran.METHODS: In this cross-sectional study, 1345 samples were collected of patients with clinical suspicions of tuberculosis that referred to health care centre of Mazandaran from July 2010 to June 2011. The specimens were cultured on Lowenstein-Jensen medium to detect the mycobacteria. DNA extraction of colonies and resistance to Isoniazid and Rifampin were evaluated by using the primers of inhA, KatG and rpoB genes.FINDINGS: Of 1345 specimens, only 65 isolates were positive culture. Out of 65, 59 were MTBC by using the primers of MUTB-gyrB gene. Among this isolates, 56 (94.92%), 55 (93.23%) and 58 (98.3%) were susceptible and 3 (5.08%), 4 (6.77%) and 1 (1.7%) were resistant to inhA, KatG and rpoB, respectively. CONCLUSION: The most resistance has been associated to Isoniazid. PCR can be a good method for identifying of the resistant strains of mycobacterium.